The roles of educators in Diabetes Mellitus prevention and management for Type 2 Diabetes Mellitus patients at Pahandut Public Health Care, Palangka Raya City - Manuntung, Alfeus; Astuti, Agnes Dewi (GHMJ (Global Health Management Journal), 2022)
Diabetes Mellitus management requires 4 pillars, namely medical nutrition therapy, medicine, exercise and health education. One of the steps that nurses can take is to provide proper health education to patients in order to increase patient independence so that diabetes management is optimal.  In Palangka Raya City, people with diabetes who come and seek treatment at the puskesmas increased quite sharply in the last 6 years, this is shown by increase in people with diabetes in the period 2006-2020. In 2020 happens a significant increase in the number of 7,615 cases of people with diabetes mellitus, this shows that health promotion has not been able to reduce the number of people with diabetes mellitus in the city of Palangka Raya. This happens because sufferers often ignore or are not aware of the dangers of DM for their lives.  This photo essay captures our efforts in controlling and monitoring the healths of the DM patients including the examination of blood sugar, blood pressure and body weight. We highlight the important role of health educators in providing health services for the entire community in order to improve the health status of the community.